Clinical course of Klebsiella variicola peritonitis in end-stage kidney disease patients receiving peritoneal dialysis - Arimuthu, Durga Arinandini; Fuah, Kar Wah; Lim, Christopher Thiam Seong (BMJ Publishing Group, 2024)
Klebsiella variicola is part of the K. pneumoniae complex and has been recently identified to have pathogenic properties. Emerging reports show that it can cause bloodstream, respiratory and urinary tract infections. It has been shown to be an important causative agent in immunocompromised individuals. We report here three cases of K. variicola peritonitis encountered in our peritoneal dialysis patients.